End-of-life decisions and practices as viewed by health professionals in pediatric critical care: A European survey study - Zanin, Anna; Brierley, Joe; Latour, Jos M.; Gawronski, Orsola (Frontiers in Pediatrics, 2023)
Background and Aim: End-of-Life (EOL) decision-making in paediatric critical care can be complex and heterogeneous, reflecting national culture and law as well as the relative resources provided for healthcare. This study aimed to identify similarities and differences in the experiences and attitudes of European paediatric intensive care doctors, nurses and allied health professionals about end-of-life decision-making and care. Methods: This is a cross-sectional observational study. An electronic survey was distributed to the European Society of Paediatric and Neonatal Intensive Care (ESPNIC) members by email and social media. The survey included three sections: (i) 16-items about attitudes toward EOL care, (ii) 14-items on EOL decisions, and (iii) 18-items about EOL care in practice. A 5-point Likert scale was used, and descriptive statistical analysis performed. Results: Overall, 198 questionnaires were completed by physicians (62%), nurses (34%) and allied health professionals (4%). Nurses reported less active involvement in decision-making processes than doctors (64% versus 95%; p<0.001). The child's expected future quality of life as viewed by the child and family was recognized as one of the most critical considerations in EOL decision-making. Sub-analysis of Northern, Central and Southern European regions revealed differences in the optimal timing of EOL decisions. Most respondents (n=179; 90%) supported discussing organ donation with parents during EOL planning. In the sub-region analysis, differences were observed in the provision of deep sedation and nutritional support during EOL care. Conclusions: This study has shown similar attitudes and experiences of EOL care among paediatric critical care professionals within European regions, but differences persist between European regions. Nurses are less involved in EOL decision-making than physicians. Further research should identify the key cultural, religious, legal and resource differences underlying these discrepancies. We recommend multi-professional ethics education to improve EOL care in European Paediatric Intensive Care.